2010
DOI: 10.1212/wnl.0b013e3181ce5d9e
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive testing, early surgery, and seizure freedom in tuberous sclerosis complex

Abstract: Background:The unambiguous identification of the epileptogenic tubers in individuals with tuber-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
75
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(82 citation statements)
references
References 15 publications
4
75
0
3
Order By: Relevance
“…We observed in the present study that preoperative epilepsy duration of 7 years or less was a significant predictor of postoperative seizure freedom. Other investigators have described a similar relationship between epilepsy duration and seizure outcomes, 41,58 sug gesting that earlier operative therapy may improve the likelihood of Engel Class I outcome. Furthermore, sev eral studies have shown that pediatric patients who at tain seizure control postoperatively may also benefit from improved intellectual and cognitive ability, 42,53 better memory function, 40 decreased medication use and side effects, 32,46 fewer behavioral problems, 45 and overall im proved quality of life 38,40 compared with patients with continued seizures.…”
Section: Discussionmentioning
confidence: 76%
“…We observed in the present study that preoperative epilepsy duration of 7 years or less was a significant predictor of postoperative seizure freedom. Other investigators have described a similar relationship between epilepsy duration and seizure outcomes, 41,58 sug gesting that earlier operative therapy may improve the likelihood of Engel Class I outcome. Furthermore, sev eral studies have shown that pediatric patients who at tain seizure control postoperatively may also benefit from improved intellectual and cognitive ability, 42,53 better memory function, 40 decreased medication use and side effects, 32,46 fewer behavioral problems, 45 and overall im proved quality of life 38,40 compared with patients with continued seizures.…”
Section: Discussionmentioning
confidence: 76%
“…However, the ability to identify epileptogenic tubers was increased with the FDG-PET/MRI-coregistered images correlating with the epileptogenic tuber removed at the time of surgery in 88% of patients. Similarly in a report by Wu and colleagues, 37 a subset of patients who were not initially considered surgical candidates were able to undergo focal resection following localization with FDG-PET/MRI coregistration.…”
Section: Novel Methods For Preoperative Evaluation In Tscmentioning
confidence: 77%
“…In 10 patients with hemispheric or generalized ictal EEG onset, magnetic source imaging was localizing in 8 patients. 37 As in other areas of epilepsy research and surgery, MEG is developing an increased role in seizure localization.…”
Section: Novel Methods For Preoperative Evaluation In Tscmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Therefore, aggressive treatment, including epilepsy surgery when applicable, is warranted. [6][7][8][9] However, identifying epileptogenic tubers is challenging because most patients have multiple lesions and multifocal epileptiform abnormalities on scalp EEG. MRI and PET with 2-deoxy-2-( 18 F) fluoro-D-glucose (FDG) can locate the tubers, but cannot identify the epileptogenic tuber(s).…”
mentioning
confidence: 99%